A influ??ncia da equipe no desempenho de projetos complexos: um estudo de m??ltiplos casos - Masini, Marcela Freitas de Souza (2020)
This research sought to study the influence of teams on the performance of five complex projects. It is a field research, exploratory and descriptive, with a qualitative approach, through the study of multiple cases in different segments (aluminum and stainless steel, automation, automotive, chemical and metro transport). As a support for the theoretical basis, a systematic literature review was carried out. The sources of data collection used were: semi structured interview, analysis of documents and records in archives. The interviews were conducted with eight respondents from complex projects that met the pre-defined profile. The questionnaire has two parts, which made it possible to highlight the aspects of the teams studied, the complexity scenario of each project and their respective performance. The data obtained were treated with the aid of the Atlas ti. software, to carry out the co-occurrence analysis, network analysis and, finally, cross analysis of the cases. The main objective was to analyze how teams influence the complex projects performance. The results obtained indicate that the complex projects performance are influenced by the teams??? characteristics, through literal replication, which revealed similar results between the cases studied. In addition, it was identified that the companies recognize the relevance of the teams and their influences on the complex projects performance, however the teams??? characteristics are scarcely managed by the companies. Most companies focus on developing technical skills, such as training and certifications. However, only a few companies mention investment in the development of behavioral aspects. Among all the characteristics addressed by the respondents, those that suggest the need for greater attention are: conflict, posture for change, proactivity, trust, teamwork, communication and resilience. The results also contribute to the discussion about the role of the teams in the projects performance, since most of the projects object of this study keep the focus mainly on the metrics of term, cost and scope (triple restriction), suggesting the need to include new aspects related to team members to improve the complex projects performance.